2017
DOI: 10.1148/radiol.2016160566
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Assessment of Renal Fibrosis with Magnetization Transfer MR Imaging: Validation and Evaluation in Murine Renal Artery Stenosis

Abstract: Purpose To test the utility of magnetization transfer imaging (MTI) in detection and monitoring the progression of renal fibrosis in mice with unilateral renal artery stenosis (RAS). Materials and Methods This prospective study was approved by the Institutional Animal Care and Use Committee. RAS (n=10) or sham surgery (n=5) was performed, and the stenotic and contralateral kidneys were studied longitudinally in-vivo at baseline and 2, 4 and 6 weeks post-surgery. Following a 16.4T MRI exam, magnetization tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 32 publications
8
80
1
Order By: Relevance
“…At baseline, CO and OSOM in the stenotic kidneys showed elevated T 1 values (P ¼ 0.031 and 0.0075, respectively) compared to the control kidneys (Fig. 5c), possibly because of edema (21). In control kidneys, R 1 showed an approximately linear increase during Mn 2þ infusion and reached a steady state during washout in CO and OSOM, but a slight decrease in ISOM (Fig.…”
Section: In Vivo T 1 Mapping By Msrfse and Validation Studymentioning
confidence: 85%
“…At baseline, CO and OSOM in the stenotic kidneys showed elevated T 1 values (P ¼ 0.031 and 0.0075, respectively) compared to the control kidneys (Fig. 5c), possibly because of edema (21). In control kidneys, R 1 showed an approximately linear increase during Mn 2þ infusion and reached a steady state during washout in CO and OSOM, but a slight decrease in ISOM (Fig.…”
Section: In Vivo T 1 Mapping By Msrfse and Validation Studymentioning
confidence: 85%
“…With a high offset-frequency, a larger flip angle is required to maintain MT contrast-to-noise ratio, but when too low, direct saturation of free water signal causes imaging artifacts. Previously, an optimal offset frequency at 1500Hz has been identified for collagen detection at 16.4T (23). Given the field dependence of the optimal offset frequency, a collagen phantom study was first performed in this study at 3.0T.…”
Section: Discussionmentioning
confidence: 99%
“…MT parameters for collagen detection in murine RAS at 16.4T were recently identified, and the applicability of MT-MRI in measuring and monitoring longitudinal progression of renal fibrosis demonstrated (23). However, its capability for detecting renal fibrosis at clinical field-strength remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] The significant differences between the cortical r values and the medullary r values suggested that the severity of fibrosis was different in the two regions. However, this study demonstrated the cortical and medullary r values elevated when obvious fibrosis appeared at week 2.…”
Section: Discussionmentioning
confidence: 99%